Genome‐wide identification and expression analyses of cytochrome P450 genes in mulberry (Morus notabilis). Issue 9 (13th March 2014) - Ma, Bi; Luo, Yiwei; Jia, Ling; Qi, Xiwu; Zeng, Qiwei; Xiang, Zhonghuai; He, Ningjia
Abstract Cytochrome P450s play critical roles in the biosynthesis of physiologically important compounds in plants. These compounds often act as defense toxins to prevent herbivory. In the present study, a total of 174 P450 genes of mulberry (Morus notabilis C.K.Schn) were identified based on bioinformatics analyses. These mulberry P450 genes were divided into nine clans and 47 families and were found to be expressed in a tissue‐preferential manner. These genes were compared to the P450 genes in Arabidopsis thaliana. Families CYP80, CYP92, CYP728, CYP733, CYP736, and CYP749 were found to exist in mulberry, and they may play important roles in the biosynthesis of mulberry secondary metabolites. Analyses of the functional and metabolic pathways of these genes indicated that mulberry P450 genes may participate in the metabolism of lipids, other secondary metabolites, xenobiotics, amino acids, cofactors, vitamins, terpenoids, and polyketides. These results provide a foundation for understanding of the structures and biological functions of mulberry P450 genes.